Development of Nursing Practice Guideline for Prevention of Hypothermia in Patients with Off Pump Coronary Artery Bypass Grafting, Udonthani Hospital - Arayawong, Tipsukon; Inthanu, Worawit; Leuluang, Weekunya (Journal of The Royal Thai Army Nurses, 2021)
The present study was a semi-experimental research for development of nursing practice guideline in order to prevent hypothermia in patients with off pump coronary artery bypass grafting in Udonthani hospital during August to October 2020. A simplified heating device in combination with a nursing practice guideline was applied for preventing the hypothermia during an operation. The collecting data tools were a patient’s temperature recording form, a satisfactory survey and an assessment form of nursing practice guideline. The data retrieved were statistical analyzed including percentage, mean value, standard deviation, paired t-test. The developed nursing care guideline in hypothermia preventing composes of 3 phases including pre-operative, intra-operative and post-operative phases. The results revealed that during the intra-operative period, the core temperatures in test group (n = 30) using wormed fluid obtained from the invented heating device were significantly higher than those for control group (n = 41) using the intermittent water warming at a statistic level of .05 (P = .003). A hundred percent of the nurses (n = 19) were excellently satisfied using the nursing practice guideline for preventing hypothermia in patients with off pump coronary artery bypass grafting. In addition, all of nurses (n = 19) followed the nursing practice guideline for preventing hypothermia in patients with off pump coronary artery bypass grafting during their duties. It can be concluded that the developed nursing practice guideline has potential to be used satisfactorily for preventing hypothermia in patients with off pump coronary artery bypass grafting.